Biomedical Mg-Gd-Nd-Zr-In alloy and preparation method thereof

By introducing Gd, Nd, Zr and In elements into the magnesium alloy, using their strong precipitation and asynchronous dissolution and deposition characteristics to form a dense degradation product film, the problem of difficult to achieve both corrosion resistance and mechanical strength of magnesium alloy is solved, and a biomedical Mg-Gd-Nd-Zr-In alloy with excellent performance was prepared.

CN119876720AActive Publication Date: 2025-04-25NORTHEASTERN UNIV CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510361209.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The corrosion resistance of existing high-strength magnesium alloys is poor, and it is difficult to have both mechanical strength and corrosion resistance, which limits its application in the biomedical field.

Method used

Using Mg-Gd-Nd-Zr-In alloy, through the strong precipitation effect of Gd and Nd elements and the asynchronous dissolution and deposition between alloy elements, a dense degradation product film is formed, which reduces the degradation rate of the alloy in simulated body fluids and achieves an effective combination of mechanical strength and corrosion resistance.

Benefits of technology

It has achieved the preparation of high-performance biomedical magnesium alloys, with excellent corrosion resistance, mechanical properties and biocompatibility, and meets the needs of clinical medical research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876720A_ABST
    Figure CN119876720A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, in particular to a biomedical Mg-Gd-Nd-Zr-In alloy and a preparation method thereof.The Mg-Gd-Nd-Zr-In alloy is prepared from, by mass, 5%-10% of Gd, 1%-5% of Nd, 0.5%-1% of Zr and 0.2%-1% of In, and the total mass percent of the Mg-Gd-Nd-Zr-In alloy is 100%. The dissolution and deposition differences among the elements are utilized to promote the formation of a compact protective film so as to improve the corrosion resistance of the alloy, and the mechanical strength of the alloy is improved by utilizing the strong precipitation effect of Gd and Nd. The alloy is excellent in mechanical property, the degradation property of the alloy in simulated body fluid is superior to that of high-purity Mg, the alloy is free of cytotoxicity and excellent in biocompatibility, and the current dual requirements for mechanics and degradation of degradable implants are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a biomedical Mg-Gd-Nd-Zr-In alloy and a preparation method thereof. Background Art

[0002] With the aging of the population and the advancement of medical technology, the demand for biomedical materials is growing. Among the many biomedical materials, degradable metal materials show great potential and advantages because they can be gradually absorbed by the human body after completing their temporary functions, avoiding the need for secondary surgery to remove them.

[0003] Magnesium and its alloys tend to have good biocompatibility, and at the same time have the characteristics of low density, high specific strength, good damping and excellent processing performance, and the mechanical properties are very similar to those of human bones, all of which make it a very promising biomedical material. However, the rapid corrosion rate of magnesium alloys and the resulting hydrogen release problem limit their clinical application. Existing commercial magnesium alloys, such as AZ31 and AZ91 containing Al elements, were originally developed for structural materials, and the safety issues as biomaterials were not fully considered. Therefore, the development of high-performance magnesium alloys with high strength and high corrosion resistance based on the biotoxicity of alloying elements is the focus of current research.

[0004] The development of high-strength magnesium alloys has gradually matured, but the corrosion resistance of these high-strength magnesium alloys is often poor. At the same time, the mechanical strength of the currently reported high-corrosion-resistant magnesium alloys is often very low. Magnesium alloys face the dilemma of having difficulty in achieving both mechanical strength and corrosion resistance. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a biomedical Mg-Gd-Nd-Zr-In alloy and a preparation method thereof. Based on the lack of high-performance biomedical magnesium alloy systems, the present invention provides a magnesium alloy with excellent corrosion resistance, mechanical properties and biocompatibility and a preparation method thereof.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A biomedical Mg-Gd-Nd-Zr-In alloy, wherein the Mg-Gd-Nd-Zr-In alloy comprises, by mass percentage: Gd: 5%~10%, Nd: 1%~5%, Zr: 0.5%~1%, In: 0.2%~1%, the remainder is Mg, totaling 100%.

[0007] The high-performance biomedical Mg-Gd-Nd-Zr-In alloy designed by the present invention first utilizes the strong precipitation effect of Gd and Nd elements to strengthen the alloy, and at the same time utilizes the asynchrony of dissolution and deposition between the alloy elements, that is, Gd and Nd elements and Mg are preferentially and rapidly dissolved, while In element is enriched on the alloy surface, and then all dissolved at once to obtain a higher interface ion concentration, and then due to the high ion concentration of In element at the interface, the deposition conditions of its corresponding degradation product are reached, so that nucleation deposition is rapidly prioritized on the surface, although a film layer completely covering the alloy surface cannot be formed, it can provide a nucleation surface for the subsequent deposition of Gd and Nd elements, reduce the nucleation energy of the degradation products of Gd and Nd deposited later, and accelerate the nucleation speed of Gd and Nd elements; the subsequent deposition of Gd and Nd will also further promote the deposition of Mg. This asynchronous dissolution and deposition will promote the formation of a dense degradation product film, thereby reducing the degradation rate of the alloy in simulated body fluids, and overall realizing the effective combination of mechanical strength and corrosion resistance of the alloy.

[0008] In addition, for the high-performance biomedical Mg-Gd-Nd-Zr-In alloy designed by the present invention, it should be noted that the content of micro / low alloying elements has a very complex and sensitive effect on corrosion resistance and mechanical properties, and the two restrain each other. Excessive content of the micro-alloying element In will hinder the dissolution of low alloying elements Gd, Nd and Mg, resulting in too low ion concentration at the interface, too few degradation products formed and insufficient protection; if the In content is too little, it cannot play a role in accelerating nucleation. If the content of low alloying elements Gd and Nd is too much, a large amount of second phase will be formed to promote micro galvanic corrosion; if the content is too little, it cannot promote the nucleation of Mg elements, and it cannot form sufficient strengthening phases, which is not conducive to the mechanical properties and corrosion resistance of the alloy. The Zr element mainly plays a role in refining the grains and improving the mechanical properties.

[0009] In a preferred embodiment of the present invention, the Mg-Gd-Nd-Zr-In alloy comprises, by mass percentage: Gd: 9%, Nd: 2%, Zr: 0.5%, In: 0.5%, Fe<0.015%, Cu<0.015%, Ni<0.005%, the remainder is Mg, totaling 100%.

[0010] The Mg-Gd-Nd-Zr-In alloy also includes impurity elements, calculated by mass percentage: impurity Fe<0.015%, Cu<0.015%, Ni<0.005%.

[0011] Another object of the present invention is to provide a method for preparing a biomedical Mg-Gd-Nd-Zr-In alloy, comprising the following steps: The raw materials Mg, In, Mg-25Gd, Mg-25Nd and Mg-20Zr master alloy were weighed and mixed according to the mass percentage of Gd: 5%~10%, Nd: 1%~5%, Zr: 0.5%~1%, In: 0.2%~1%, Fe<0.015%, Cu<0.015%, Ni<0.005%, and the balance was Mg, totaling 100%.

[0012] The symmetrically taken raw materials are heated, melted and stirred under a protective atmosphere to carry out a homogenization treatment.

[0013] The homogenized raw material is cast to obtain a Mg-Gd-Nd-Zr-In alloy ingot, and the Mg-Gd-Nd-Zr-In alloy ingot is turned or milled to remove the oxide layer and skin defects on the surface.

[0014] The Mg-Gd-Nd-Zr-In alloy ingot after turning or milling is heated and kept warm, and then hot extruded to obtain an extruded rod.

[0015] The extruded rod is subjected to aging treatment to obtain a high-performance biomedical Mg-Gd-Nd-Zr-In alloy.

[0016] In a preferred embodiment of the present invention, the hot extrusion temperature is 400° C. to 450° C., the extrusion ratio is 8 to 10:1, and the extrusion rate is 0.3 mm / s to 0.5 mm / s.

[0017] In a preferred embodiment of the present invention, the aging treatment temperature is 180° C. to 250° C., and the aging treatment time is 80 hours to 100 hours.

[0018] In a preferred embodiment of the present invention, when the hot extrusion treatment is performed, the heating and heat preservation temperature is 400° C. to 450° C., and the heat preservation time is 1 hour to 2 hours.

[0019] In a preferred embodiment of the present invention, the heating temperature during the homogenization treatment is 700°C to 740°C.

[0020] In a preferred embodiment of the present invention, the protective atmosphere is CO2 and SF6 in a volume ratio of 9:1.

[0021] In a preferred embodiment of the present invention, the purity of the raw materials Mg and In is greater than 99.9%.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The high-performance biomedical Mg-Gd-Nd-Zr-In alloy designed by the present invention first utilizes the strong precipitation effect of Gd and Nd elements to strengthen the alloy, and at the same time utilizes the asynchrony of dissolution and deposition between the alloy elements, that is, Gd and Nd elements and Mg are preferentially and rapidly dissolved, while In element is enriched on the alloy surface, and then all dissolved at once to obtain a higher interface ion concentration, and then due to the high ion concentration of In element at the interface, the deposition conditions of its corresponding degradation product are reached, so that nucleation deposition is rapidly prioritized on the surface, although a film layer that completely covers the alloy surface cannot be formed, it can provide a nucleation surface for the subsequent deposition of Gd and Nd elements, reduce the nucleation energy of the degradation products of Gd and Nd deposited later, and accelerate the nucleation speed of Gd and Nd elements; the subsequent deposition of Gd and Nd will further promote the deposition of Mg. This asynchronous dissolution and deposition will promote the formation of a dense degradation product film, thereby reducing the degradation rate of the alloy in simulated body fluids, and overall achieving an effective combination of the mechanical strength and corrosion resistance of the alloy.

[0023] 2. The high-performance biomedical Mg-Gd-Nd-Zr-In alloy designed by the present invention should be noted that the content of micro / low alloying elements has a very complex and sensitive effect on corrosion resistance and mechanical properties, and the two restrain each other. Excessive content of the micro-alloying element In will hinder the dissolution of low alloying elements Gd, Nd and Mg, resulting in too low ion concentration at the interface, too few degradation products formed and insufficient protection; if the In content is too little, it cannot accelerate nucleation. If the content of low alloying elements Gd and Nd is too much, a large amount of second phase will be formed to promote micro galvanic corrosion; if the content is too little, it cannot promote the nucleation of Mg elements, and cannot form sufficient strengthening phases, which is not conducive to the mechanical properties and corrosion resistance of the alloy. The Zr element mainly plays the role of refining the grains and improving the mechanical properties.

[0024] 3. The high-performance biomedical magnesium alloy Mg-9Gd-2Nd-0.5Zr-0.5In designed by the present invention has better degradation performance in simulated body fluids than high-purity magnesium, and can form a very dense degradation product layer with a certain thickness. The alloy exhibits excellent degradation performance.

[0025] 4. The high-performance biomedical magnesium alloy Mg-9Gd-2Nd-0.5Zr-0.5In designed by the present invention has excellent biocompatibility, has a beneficial effect on cell proliferation, has high cell activity and is non-cytotoxic. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison diagram of stress-strain curves of alloys prepared in Example 1 and Example 2 of the present invention.

[0027] Figure 2The following are surface electron microscope scanning photographs of corrosion products of the test samples obtained from (a) Example 1 of the present invention and (b) Comparative Example 1 after long-term immersion.

[0028] Figure 3 The following are surface electron microscope scanning photographs of the test samples obtained in (a) Example 1 of the present invention and (b) Comparative Example 1 after long-term immersion and removal of corrosion products.

[0029] Figure 4 2D laser confocal images of the test samples obtained in (a) Example 1 of the present invention and (b) Comparative Example 1 after removing surface corrosion products.

[0030] Figure 5 The electrochemical impedance spectra of the test samples obtained in Example 1 of the present invention are regularly monitored during the long-term immersion period, (a) is immersion for 0 to 30 days, (b) is immersion for 36 to 60 days, and (c) is immersion for 66 to 90 days, wherein Z' represents the real part of the impedance, and Z" represents the imaginary part of the impedance.

[0031] Figure 6 This is a statistical result diagram of electrochemical impedance calculation of the test sample prepared in Example 1 of the present invention and the commercial high-purity magnesium test sample of the comparative example.

[0032] Figure 7 Fluorescence microscopic images of mouse embryonic osteoblast precursor cells in the alloy prepared in Example 1 of the present invention, the commercial high-purity magnesium of the comparative example, and the blank group implant.

[0033] Figure 8 (a) Statistical graph of absorbance and (b) Statistical graph of relative cell proliferation rate of mouse embryonic osteoblast precursor cells after being cultured in the alloy prepared in Example 1 of the present invention, the commercial high-purity magnesium in Comparative Example 1 and the blank group implant. DETAILED DESCRIPTION

[0034] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0036] The present invention aims to solve a series of problems such as insufficient mechanical strength and corrosion resistance of biomedical magnesium alloys, and proposes a biomedical Mg-Gd-Nd-Zr-In alloy and a preparation method. The conventional three-electrode system is used for electrochemical testing, and the degradation rate of the alloy is analyzed by electrochemical impedance spectroscopy and polarization curves. The mechanical properties of the alloy are evaluated by tensile tests, and the biocompatibility of the alloy is evaluated by cytotoxicity experiments. The results show that the corrosion potential and corrosion current density are obtained by Tafel extrapolation of the polarization curve, and the corrosion rate is calculated. The corrosion rate of the alloy in simulated body fluid is significantly lower than that of high-purity Mg. The polarization resistance under long-term immersion is statistically analyzed, and the degradation performance of the alloy is significantly better than that of high-purity Mg. According to the results of the tensile test, the yield strength, tensile strength and elongation at break of the alloy after aging are 307.29±7.19 MPa, 321.78±3.65 MPa and 24.78±2.95%, respectively, and the mechanical strength and plasticity are excellent. Combined with the results of the cytotoxicity test, the alloy is non-cytotoxic and has no effect on cell morphology. In summary, the high-performance biomedical Mg-Gd-Nd-Zr-In alloy of the present invention meets the multiple requirements of current degradable implants for mechanical strength, degradation performance and biocompatibility, and is expected to be implemented in clinical medical research.

[0037] Example 1 A method for preparing a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-9Gd-2Nd-0.5Zr-0.5In.

[0038] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0039] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0040] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 400°C for 2 hours, and then extruded at 400°C with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s to obtain a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy.

[0041] Example 2 A method for preparing a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-9Gd-2Nd-0.5Zr-0.5In.

[0042] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0043] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0044] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and skin defects on the surface of the ingot, and then kept at 400° C. for 2 hours, and then extruded at 400° C. with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s.

[0045] (5) The magnesium alloy extruded rod in step (4) is kept at 200° C. for 96 hours for aging treatment to obtain a fine precipitate phase in the matrix structure, thereby obtaining a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy.

[0046] Example 3 A method for preparing a high-performance biomedical Mg-5Gd-1Nd-0.5Zr-0.2In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-5Gd-1Nd-0.5Zr-0.2In.

[0047] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0048] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0049] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 400°C for 2 hours, and then extruded at 400°C with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s to obtain a high-performance biomedical Mg-5Gd-1Nd-0.5Zr-0.2In alloy.

[0050] Example 4 A method for preparing a high-performance biomedical Mg-10Gd-5Nd-1Zr-1In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-10Gd-5Nd-1Zr-1In.

[0051] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0052] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0053] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 400°C for 2 hours, and then extruded at 400°C with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s to obtain a high-performance biomedical Mg-10Gd-5Nd-1Zr-1In alloy.

[0054] Example 5 A method for preparing a high-performance biomedical Mg-7Gd-3Nd-0.8Zr-0.7In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-7Gd-3Nd-0.8Zr-0.7In.

[0055] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0056] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0057] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 400°C for 2 hours, and then extruded at 400°C with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s to obtain a high-performance biomedical Mg-7Gd-3Nd-0.8Zr-0.7In alloy.

[0058] Example 6 A method for preparing a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-9Gd-2Nd-0.5Zr-0.5In.

[0059] (2) The raw materials prepared in step (1) are placed in a graphite crucible, heated in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and kept warm at 700°C. After the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0060] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0061] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 420°C for 1 hour, and then extruded at 420°C with an extrusion ratio of 8 and an extrusion rate of 0.3 mm / s to obtain a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy.

[0062] Example 7 A method for preparing a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-9Gd-2Nd-0.5Zr-0.5In.

[0063] (2) The raw materials prepared in step (1) are placed in a graphite crucible, heated in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and kept warm at 740°C. After the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0064] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0065] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 450° C. for 1.5 hours, and then extruded at 450° C. with an extrusion ratio of 10 and an extrusion rate of 0.5 mm / s to obtain a high-performance biomedical Mg-9Gd-2Nd-0.5Zr-0.5In alloy.

[0066] Comparative Example 1 Generally, due to the segregation of alloying elements and the presence of second phase particles in the structure, the corrosion rate of magnesium alloy is much higher than that of high-purity magnesium. Reducing the corrosion rate of magnesium alloy can usually only infinitely approach the corrosion rate of high-purity magnesium. Therefore, in the present invention, commercial high-purity magnesium with a purity of 99.99% is used as a comparative example.

[0067] Comparative Example 2 A method for preparing a biomedical Mg-4Gd-0.5Nd-0.5Zr-0.1In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-4Gd-0.5Nd-0.5Zr-0.1In.

[0068] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0069] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0070] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 400°C for 2 hours, and then extruded at 400°C with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s to obtain a biomedical Mg-4Gd-0.5Nd-0.5Zr-0.1In alloy.

[0071] Comparative Example 3 A method for preparing a biomedical Mg-11Gd-6Nd-1.5Zr-1.5In alloy comprises the following steps: (1) High-purity Mg and high-purity In with a purity greater than 99.9% and Mg-25Gd, Mg-25Nd, and Mg-20Zr master alloys are prepared according to the composition of Mg-11Gd-6Nd-1.5Zr-1.5In.

[0072] (2) Place the raw materials prepared in step (1) into a graphite crucible, heat them in a protective atmosphere of CO2 and SF6 with a volume ratio of 9:1, and keep them warm at 720°C. After ensuring that the raw materials are completely melted, mechanical stirring is performed for 10 minutes to ensure that the raw materials are evenly mixed. After that, the raw materials are allowed to stand for 10 minutes, slag is removed, and then allowed to stand for 15 minutes.

[0073] (3) The raw material in the crucible in step (2) is cast into a sand mold to obtain a cylindrical ingot.

[0074] (4) The ingot obtained in step (3) is turned or milled to remove the oxide layer and surface defects on the surface of the ingot, and then kept at 400°C for 2 hours, and then extruded at 400°C with an extrusion ratio of 9 and an extrusion rate of 0.4 mm / s to obtain a biomedical Mg-11Gd-6Nd-1.5Zr-1.5In alloy.

[0075] Examples 3 to 7 are high-performance biomedical Mg-Gd-Nd-Zr-In alloys prepared by changing the amount of alloying elements and process conditions. Comparative Examples 2 and 3 are Mg-Gd-Nd-Zr-In alloys prepared by changing the percentage of different alloying elements. The content of micro / low alloying elements in the alloy designed by the present invention has a very complex and sensitive effect on corrosion resistance and mechanical properties, and the two are mutually restrained. Excessive content of the micro-alloying element In will hinder the dissolution of low alloying elements Gd, Nd and Mg, resulting in too low ion concentration at the interface, too few degradation products formed and insufficient protection; if the In content is too little, it cannot play a role in accelerating nucleation. If the content of low alloying elements Gd and Nd is too much, a large amount of second phases will be formed to promote micro galvanic corrosion; if the content is too little, it cannot play a role in promoting the nucleation of Mg elements, and it cannot form sufficient strengthening phases, which is not conducive to the mechanical properties and corrosion resistance of the alloy. Therefore, the alloys obtained in Comparative Examples 2 and 3 cannot simultaneously achieve effective improvement of mechanical properties and corrosion resistance.

[0076] The Mg-9Gd-2Nd-0.5Zr-0.5In alloy rods after aging treatment were wire-cut and made into 20 mm × 20 mm × 5 mm and sheet-shaped dog-bone tensile specimens, respectively. The tensile specimens had a gauge length of 15 mm, a width of 3.6 mm, and a thickness of 2.5 mm, so as to facilitate subsequent electrochemical testing and room temperature tensile testing. SiC sandpaper was used for grinding before testing.

[0077] The room temperature tensile properties were tested according to GB / T 228.1-2010 “Metallic materials tensile tests Part 1: Room temperature test methods” using an INSTRON 55822 electronic universal testing machine.

[0078] After the sample is connected to a copper wire, it is embedded in epoxy resin, and the connection between the sample and the wire is sealed in epoxy resin. After the epoxy resin solidifies, the surface of the sample not connected to the wire is grinded with 140 mesh, 600 mesh, 1200 mesh and 2000 mesh sandpaper respectively to expose the material surface and use it as the test surface. The area of ​​the test surface is measured and recorded. Afterwards, the sample is used as the anode, the platinum wire as the counter electrode, and the calomel reference electrode is inserted near the sample test surface as the reference electrode. The impedance spectrum and polarization curve of the sample after being immersed in simulated body fluid for different time periods are tested using an electrochemical workstation.

[0079] Before the electrochemical impedance spectroscopy test, the samples were stabilized for 30 min to 60 min, the test frequency was 100 kHz to 10 mHz, and the amplitude was set to 10 mV.

[0080] The chromic acid solution used to clean the degradation products on the sample surface consisted of 200 g / L CrO3 and 10 g / L AgNO3.

[0081] After the test, the samples were taken out, the degradation products were cleaned with chromic acid, and the degradation morphology was characterized under a scanning electron microscope. The depth of local corrosion pits on the sample surface was measured using laser confocal microscopy.

[0082] The leaching solution of Mg-Gd-Nd-Zr-In alloy was prepared and the cytotoxicity of the alloy was tested. The specific operation was as follows: (1) Cut the Mg-Gd-Nd-Zr-In alloy into cylinders with a diameter of 10 mm and a height of 2 mm. Polish them with 800#, 1000#, 1500# and 2000# sandpapers in sequence, clean them with anhydrous ethanol by ultrasonic vibration for 5 minutes, and blow dry them for later use.

[0083] (2) Mouse embryonic osteoblast precursor cells were added to modified minimum essential MEM (α-MEM) medium containing 10% by volume of fetal bovine serum (FBS), placed in a cell culture incubator at 37°C and 5% by volume of CO2, and digested and passaged using 0.25% by volume of trypsin.

[0084] (3) Place the sample in a 24-well plate and follow the ISO10993 international standard at 1.25 cm 2 / mL of immersion ratio was immersed in α-MEM culture medium containing 10% FBS volume fraction, and placed in a cell culture incubator at 37°C and 5% CO2 volume fraction to prepare the extract. After that, the extract volume fraction was diluted 6 times for in vitro cytotoxicity experiment.

[0085] (4) 100 μL of 3×10 4 / mL MC3T3-E1 cell suspension was inoculated in a 96-well plate, with 5 wells in each group, and cultured in a cell culture incubator at 37°C and 5% CO2 for 24 hours. After the cells adhered to the wall and grew, the original culture medium was discarded, and 100 μL of Mg-Gd-Nd-Zr-In alloy extract was added to each well. The control group was α-MEM culture medium containing 10% volume fraction FBS, and the culture was continued. The 96-well plate was taken out after 24, 48 and 72 hours, and the supernatant was carefully aspirated. After rinsing with phosphate buffered saline (PBS) for 3 times, 100 μL of α-MEM culture medium containing 10% volume fraction CCK 8 reagent was added to each well and cultured for 2 hours. The cell OD value of each well was measured with an automatic microplate reader at a wavelength of 450 nm to calculate the cell survival rate.

[0086] During the sample immersion process, the water bath temperature is set to 37°C to simulate the temperature of the human body. The simulated body fluids can be SBF, Hank's solution, MEM, etc.

[0087] In the long-term immersion experiment of samples, the simulated body fluid was replaced every 24 hours to eliminate the influence of the change of pH value of the simulated body fluid on the test results.

[0088] Results Analysis Figure 1 The stress-strain curves of the alloys prepared in Examples 1 and 2 of the present invention are as follows: Figure 1 As shown, the yield strength, tensile strength and elongation at break of the alloy prepared in Example 1 are 307.29±7.19 MPa, 321.78±3.65 MPa and 24.78±2.95%, respectively; the yield strength, tensile strength and elongation at break of the alloy prepared in Example 2 are 272.66±5.12 MPa, 300.67±2.18 MPa and 26.38±2.28%, respectively. Both Example 1 and Example 2 have excellent mechanical properties.

[0089] Figure 2 The surface electron microscope scanning images of the corrosion products of the test samples obtained in Example 1 of the present invention and Comparative Example 1 after long-term immersion; wherein (a) is Example 1, (b) is Comparative Example 1, as shown in FIG. Figure 2 As shown in the figure, after long-term immersion, due to the asynchrony of dissolution and deposition between alloy elements, the surface of the sample in Example 1 has been completely covered with corrosion products, and the corrosion products are densely stacked, while the corrosion product particles on the surface of the sample in Comparative Example 1 are fine, and cracks appear due to dehydration of the surface layer. The formation of a dense degradation product layer greatly reduces the degradation rate of Example 1.

[0090] Figure 3 The surface electron microscope scanning images of the test samples obtained in Example 1 of the present invention and Comparative Example 1 after long-term immersion and removal of corrosion products; wherein (a) is Example 1, (b) is Comparative Example 1, as shown in FIG. Figure 3 As shown, after a long period of immersion, there is no serious local corrosion on the surface of Example 1, while Comparative Example 1 exhibits relatively serious local corrosion, which indicates that Example 1 can undergo uniform degradation.

[0091] Figure 4 2D laser confocal images of the test samples obtained in Example 1 of the present invention and the comparative example after removing the surface corrosion products; wherein (a) is Example 1, and (b) is Comparative Example 1, as shown in FIG. Figure 4 As shown, in the section with the largest line roughness, Example 1 is significantly lower than Comparative Example 1, which also reflects that the local corrosion of Comparative Example 1 is more serious.

[0092] Figure 5 The electrochemical impedance spectra of the test samples obtained in Example 1 of the present invention are regularly monitored during the long-term immersion period; wherein (a) is immersion in Example 1 for 0-30 days, (b) is immersion in Example 1 for 36-60 days, and (c) is immersion in Example 1 for 66-90 days. Figure 5 As shown in the figure, the impedance on the electrochemical spectrum is always within 10 4 This result indicates that the dense degradation product layer formed on the surface of the alloy provides continuous protection for the alloy matrix.

[0093] Figure 6 The corrosion rate of Example 1 of the present invention and the commercial high-purity magnesium in the comparative example changes with time according to electrochemical impedance fitting. After immersion for 15 days, the degradation rates of Example 1 and the commercial high-purity magnesium in the comparative example are close. After 15 days, the difference in degradation rates between the two gradually increases, and the degradation rate of Example 1 is significantly lower than that of the commercial high-purity magnesium in the comparative example.

[0094] Figure 7The fluorescence microscopic images of the cells of mouse embryonic osteoblast precursor cells after co-culture in Example 1 of the present invention and the commercial high-purity magnesium leaching solution of the comparative example for 1-3 days. As the number of cells in the three groups of experiments increased with the extension of the culture days, the morphology was similar, which shows that Example 1 had no effect on the cell morphology.

[0095] Figure 8 The graphs are the absorbance statistics and relative cell proliferation rate statistics of the precursor cells of mouse embryonic osteoblasts after being cultured in the commercial high-purity magnesium extract of Example 1 of the present invention and the comparative example for different days. Among them, (a) is the absorbance statistics graph, and (b) is the relative cell proliferation rate statistics graph. Figure 8 As shown, the cell activity and relative cell proliferation rate of Example 1 were higher than those of the comparative commercial high-purity magnesium on the third day, and the cytotoxicity was level 0, which indicated that Example 1 had excellent biocompatibility.

[0096] In summary, the high-performance biomedical Mg-Gd-Nd-Zr-In alloy prepared by the present invention has high mechanical strength, excellent degradation performance, no cytotoxicity, and excellent biocompatibility. It meets the current multiple requirements of degradable implants for mechanical strength, degradation performance and biocompatibility, and is expected to be implemented in clinical medical research.

[0097] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0098] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations.

Claims

1. A biomedical Mg-Gd-Nd-Zr-In alloy, characterized in that: In terms of mass percentage, the Mg-Gd-Nd-Zr-In alloy comprises: Gd: 5%~10%, Nd: 1%~5%, Zr: 0.5%~1%, In: 0.2%~1%, the remainder is Mg, totaling 100%.

2. The biomedical Mg-Gd-Nd-Zr-In alloy according to claim 1, characterized in that: In terms of mass percentage, the Mg-Gd-Nd-Zr-In alloy comprises: Gd: 9%, Nd: 2%, Zr: 0.5%, In: 0.5%, and the balance is Mg, totaling 100%.

3. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 1, characterized in that: The following steps are involved: Weigh raw materials Mg, In, Mg-25Gd, Mg-25Nd and Mg-20Zr master alloy, and mix them according to the mass percentage of Gd: 5%~10%, Nd: 1%~5%, Zr: 0.5%~1%, In: 0.2%~1%, and the balance is Mg, which is 100% in total; The symmetrically taken raw materials are heated, melted and stirred under a protective atmosphere to perform a homogenization treatment; Casting the homogenized raw material to obtain a Mg-Gd-Nd-Zr-In alloy ingot, turning or milling the Mg-Gd-Nd-Zr-In alloy ingot to remove the oxide layer and skin defects on the surface; The Mg-Gd-Nd-Zr-In alloy ingot after turning or milling is heated and kept warm, and then subjected to hot extrusion treatment to obtain the biomedical Mg-Gd-Nd-Zr-In alloy.

4. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 3, characterized in that: The hot extrusion temperature is 400℃~450℃, the extrusion ratio is 8~10:1, and the extrusion rate is 0.3 mm / s~0.5 mm / s.

5. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 4, characterized in that: When hot extrusion treatment is performed, the heating and insulation temperature is 400°C to 450°C, and the insulation time is 1 hour to 2 hours.

6. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 3, characterized in that: When the homogenization treatment is performed, the heating temperature is 700°C~740°C.

7. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 3, characterized in that: The alloy after hot extrusion treatment is subjected to aging treatment to obtain a biomedical Mg-Gd-Nd-Zr-In alloy.

8. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 7, characterized in that: The aging treatment temperature is 180°C~250°C, and the aging treatment time is 80 hours~100 hours.

9. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 3, characterized in that: The protective atmosphere is CO2 and SF6 in a volume ratio of 9:

1.

10. The method for preparing the biomedical Mg-Gd-Nd-Zr-In alloy according to claim 3, characterized in that: The purity of raw materials Mg and In is greater than 99.9%.

Citation Information

Patent Citations

  • Magnesium-based alloy

    CN101702923A

  • High-strength high-toughness corrosion-resistant flame-proof Mg-Gd-Y-Zn-Zr alloy and preparation method thereof

    CN106756370A

  • High-strength and high-toughness magnesium alloy containing Sc and preparation method thereof

    CN109022983A

  • Corrosion-resistant biological magnesium-indium alloy as well as preparation method and application thereof

    CN110541098A

  • Degradable compositions, apparatus comprising same, and methods of use

    GB0700919D0